Homegoing [book club bag] - Gyasi, Yaa (Alfred A. Knopf, 2016)
"Two half sisters, Effia and Esi, unknown to each other, are born into two different tribal villages in 18th century Ghana. Effia will be married off to an English colonial, and will live in comfort in the sprawling, palatial rooms of Cape Coast Castle, raising half-caste children who will be sent abroad to be educated in England before returning to the Gold Coast to serve as administrators of the Empire. Her sister, Esi, will be imprisoned beneath Effia in the Castle's women's dungeon, and then shipped off on a boat bound for America, where she will be sold into slavery. Stretching from the tribal wars of Ghana to slavery and Civil War in America, from the coal mines in the north to the Great Migration to the streets of 20th century Harlem, Yaa Gyasi's has written a modern masterpiece, a novel that moves through histories and geographies and--with outstanding economy and force--captures the troubled spirit of our own nation"--